Eco-based polymers: A review concerning bioplastics with greater manufacturing potential - Rossetto, Leonardo Luís; Vianna, Nycollas Stefanello; Mossi, Altemir José; Treichel, Helen (Seven Editora, 2024)
Currently, it is almost impossible to imagine a world without plastics. These are widely used in various sectors of the economy, such as packaging, construction, transport, healthcare, and electronics, due to their low cost, versatility, durability, and high strength/weight ratio. However, the durability of plastics after use becomes an environmental problem, as a large part of plastic waste ends up in landfills, is incinerated, or discarded illegally, contaminating ecosystems and contributing to global warming. A promising alternative to mitigate these impacts is the development of bioplastics, which are bio-based, biodegradable materials, or both. Bioplastics include poly(lactic acid) (PLA), polyhydroxyalkanoates (PHA), bio-based polyamide (PA), and polypropylene (PP), which have the potential to replace conventional plastics in various applications. Global production of bioplastics is growing, estimated to reach 7.43 million tons by 2028, driven by demand for more sustainable alternatives. Despite challenges, such as high production costs and even inferior properties compared to synthetic plastics, investments in research and development promise to improve these materials. This scope reviews the bioplastics with the most significant manufacturing potential in the coming years. With technological advancement and growing environmental awareness, bioplastics are expected to be crucial in transitioning to a low-carbon circular economy. DOI:https://doi.org/10.56238/sevened2024.026-027